A-185 An Analysis of Rarely Missed Items on the TOMM. (30th August 2021) - Harrell, Murphy; Myers, Melissa; Hawley, Nanako; Pizer, Jasmin; Hill, Benjamin
Abstract: Objective: This study examined item performance on Trial 1 of the Test of Memory Malingering (TOMM). We also identified items that were most often missed in individuals with genuine effort. Method: Participants were 106 adults seen for disability claims (87.7% male; 70.5% Caucasian, 26.7% Black; age range 22–84 years, Mage = 44.42 years, SD = 13.07; Meducation = 13.58, SD = 2.05) who completed and passed the TOMM as part of a larger battery. Mean score Trial 1 was 43.08, SD = 5.49. Mean score on Trial 2 was 48.98, SD = 1.54. Results: Frequency analysis indicated that >95% of the sample correctly identified six items on Trial 1: item 1-spinning wheel (97.2%), item 8-musical notes (99.1%), item 38-ice cream (98.1%), item 41-life preserver (95.3%), item 45-iron (95.3%), and item 47-dart (98.1%). Nine items were correctly identified on Trial 1 by <80% of the sample: item 2-tissue box (77.4%), item 6-suitcase (77.4%), item 20-motorcycle (77.4%), item 22-jack-in-the box (71.7%), item 26-light bulb (75.5%), item 27-maple leaf (72.6%), item 32-racket (79.2%), item 36-birdhouse (79.2%), item 44-pail & shovel (66.0%). Conclusions: These findings suggest that items on Trial 1 of the TOMM differ in difficulty in a disability claims sample who performed genuinely on the TOMM. Items 1, 8, 38, 41, 45, and 47 are good candidates for a rarely missed index where failure of these items would be probabilistically unlikely. Future research should evaluate whether these items are failed at higher rates in cases of borderline TOMM performance to improve sensitivity to feigning.